Equivocal evidence for a change in balance between selfing and pollinator‐mediated reproduction in annual Brassicaceae growing along a rainfall gradient. Issue 1 (8th June 2020) - Gibson‐Forty, Eleanor V. J.; Tielbörger, Katja; Seifan, Merav
Abstract: Because many plants ensure their reproductive success using some level of self‐fertilization, it is predicted that the balance between pollinator‐mediated pollen transfer and autonomous selfing will be correlated with habitat harshness and pollinator activity. To study these correlations, we used three annual species that differ in their self‐incompatibility and compared their reproductive success in the form of fruit production and seed viability, with and without pollinators, along a rainfall gradient and in relation to pollinator activity. We found that pollinator activity decreased with increasing aridity. Although the reproductive success in the absence of pollinators fitted the species' level of self‐incompatibility, no clear trend was detected between pollinator visits or site harshness and relative reproductive success. Only one of the species, Sinapis alba, showed a consistent increase in autonomous selfing with both increased aridity and decreased pollinator visits, a finding that was supported by an increase in the viability of seeds produced in the absence of pollinators. Nevertheless, unlike our prediction, the absolute number of seeds produced per S. alba flower increased with aridity. Our overall findings suggest that despite decreasing pollinator abundance and diversity with increasing aridity, the reproductive success of annual species, even of those with high self‐incompatibility, remains relatively high. Although there may be several mechanisms governing these results, the overall constant seed production despite environmental uncertainties may be part of the mechanism by which plants in arid ecosystems buffer environmental variations.